THE EFFECTIVENESS OF INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) IN LEARNING ISLAMIC EDUCATION - Waluyo Erry Wahyudi (AL-ISHLAH: Jurnal Pendidikan, 2020)
The purpose of this research was to know the effectiveness of information and communication technology (ICT) in learning Islamic education in junior high school tunas dharma Lampung Selatan. The technique of data analysis used qualitative analysis, namely the research discussesed about the problem how the effectiveness of information and communication technology (ICT) in learning islamic education in junior high school tunas dharma Lampung Selatan. Based on the results of the data from the research and after the data was analyzed, it can be concluded that the Application of Information and Communication Technology (ICT) runs effectively realized by several indicators included: In the learning process which used the Internet as outlined in the RPP, able to create and design on the web, able to answer issues related to Information and communication Technology (ICT) which contained in interviews and increase students learning result of Class IX A. The average score on the cognitive side, namely above the KKM was 29 students or 80.55% and below the KKM was 7 students or 19.44%.